2015
DOI: 10.1111/jdv.13067
|View full text |Cite
|
Sign up to set email alerts
|

In vivo reflectance confocal microscopy of equivocal melanocytic lesions detected by digital dermoscopy follow‐up

Abstract: Reflectance confocal microscopy evaluation of equivocal lesions detected by DFU improved the accuracy in the detection of melanoma. The combination of dermoscopy, DFU and confocal microscopy in equivocal lesions can be useful to dramatically reduce the number of excisions of benign lesions in atypical mole syndrome patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 27 publications
1
57
0
Order By: Relevance
“…8,19 Several studies have demonstrated that focal dermoscopic structural changes are significantly associated with melanoma, however; it remains extremely difficult to differentiate changing atypical nevi from early melanoma via dermoscopy. 20 …”
Section: Role Of Reflectance Confocal Microscopy In Detecting Melanommentioning
confidence: 99%
See 1 more Smart Citation
“…8,19 Several studies have demonstrated that focal dermoscopic structural changes are significantly associated with melanoma, however; it remains extremely difficult to differentiate changing atypical nevi from early melanoma via dermoscopy. 20 …”
Section: Role Of Reflectance Confocal Microscopy In Detecting Melanommentioning
confidence: 99%
“…8 If RCM is added as another investigative layer, approximately 70% of the excisions of changing or equivocal nevi could potentially be avoided without decreasing the sensitivity for melanoma detection. 20,21 Table 1 summarizes the RCM features used to help differentiate melanoma from nevi. The main RCM features associated with melanoma include the presence of roundish pagetoid cells, atypical cells at the basal layer, non-edged papilla, and nucleated atypical cells within the dermis.…”
Section: Role Of Reflectance Confocal Microscopy In Detecting Melanommentioning
confidence: 99%
“…However, 8% of monitored lesions excised due to change are benign [70]. RCM can be used as an adjunct in atypical melanocytic lesions exhibiting changes on digital dermoscopy follow-up to further improve diagnostic accuracy of melanoma [17,19,71]. Lovatto  et al .…”
Section: Background: Reflectance Technologymentioning
confidence: 99%
“…Lovatto  et al . retrospectively evaluated the impact of RCM evaluation in melanocytic lesions exhibiting changes on digital dermoscopy surveillance [17]. In a series of 64 lesions (13 MIS, 5 SSM, 51 benign nevi), confocal microscopy analysis showed a sensitivity and specificity of 100 and 69%, respectively, for the diagnosis of melanoma and could have avoided excision of 35 of 51 benign nevi.…”
Section: Background: Reflectance Technologymentioning
confidence: 99%
“…Dermatologists diagnose MM according to ABCDE rule (asymmetry, border, color, diameter, and evolution). The major disadvantage of these two types of methods is the heavily dependence on the expertise and training of the dermatologist [14,15]. Due to this fact, this method causes high rate of false positive alarms.…”
Section: Introductionmentioning
confidence: 99%